(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the linguistic and semantic features of railway terminology. The study explores the use of international, Russian, and local terms in the Uzbek language, highlighting their national, cultural, and technical significance. The role of translation strategies such as transliteration, adaptation, and equivalent word formation in term analysis is examined. The results confirm the dominance of international terms but emphasize the necessity of developing national terminology and aligning it with global standards. This work provides guidelines for systematizing terms and their practical application for specialists in linguistics and technical fields.